The efficacy and safety of electrical acupoint stimulation (EAS) for knee osteoarthritis (KOA): A GRADE-assessed systematic review, meta-analysis and trial sequential analysis - Guangyi Yang; Rong Zhang; Botan Xu; Yi Yang; Yuxuan Wang; Wenjing Xu; Pengwei Li; Aotian Yu; Simin Ning; Qixuan Fu; Jianfeng Tu (PLoS ONE, 2025)
Electrical acupoint stimulation (EAS) is proposed as a potentially beneficial treatment for patients suffering from knee osteoarthritis (KOA). This systematic review and meta-analysis aims to assess the assess the effectiveness and safety of EAS for KOA. To identify eligible RCTs, a systematic search for eligible RCTs is conducted through 6 November 2024 in 12 electronic literature databases, utilizing relevant keywords. The analysis applies a random-effects model to compute RRs and 95% CIs for the dichotomous outcome, alongside the SMD and 95% CIs for continuous outcomes. This meta-analysis includes 63 RCTs with a total of 6475 participants. The pooled analysis reveals that EAS increases the overall response rate by 19.5% (RR: 1.195, 95% CI: 1.130 to 1.264, P < 0.001; low certainty). For continuous outcomes, EAS produces large effects on WOMAC total score (SMD = −1.72, 95% CI −2.19 to −1.24; P < 0.001; low certainty), VAS score (SMD = −1.92, 95% CI −2.44 to −1.39; P < 0.001; very low certainty), WOMAC stiffness (SMD = −1.12, 95% CI −1.65 to −0.59; P < 0.001; low certainty) and Lysholm score (SMD = 1.10, 95% CI 0.47 to 1.73; P = 0.001; low certainty). It yields medium effects on WOMAC pain (SMD = −0.74, 95% CI −1.10 to −0.37; P < 0.001; low certainty), Lequesne index (SMD = −0.70, 95% CI −0.97 to −0.42; P < 0.001; low certainty) and WOMAC function (SMD = −0.51, 95% CI −0.97 to −0.05; P = 0.03; low certainty). There are no significant effects on peak quadriceps torque (SMD = 0.21, 95% CI −0.42 to 0.83; P = 0.518; low certainty) or knee range of motion (SMD = 0.66, 95% CI −0.07 to 1.38; P = 0.077; low certainty). Trial sequential analysis indicates that the required information size is met. This review suggests that EAS may be an effective and relatively safe adjunctive option for KOA; however, the certainty of the evidence is low due to substantial heterogeneity and potential biases. Higher-quality, rigorously designed RCTs with standardized reporting are needed to confirm these findings.